Histomorphological patterns of lesions in lymph node biopsies - Sidra Bibi , Kainaat Ali , Aasiya Niazi , Sidra Bibi , Kainaat Ali , Aasiya Niazi (Journal of Rawalpindi Medical College, 2021)
Introduction: Lymph node biopsies are routinely performed for the evaluation of lymphadenopathies. Tuberculosis and other infections are the major causes of lymphadenopathy in developing countries. The pattern of lymph node enlargement is different for different age groups. Malignancies are common in adults as compared to children. Objective: To document the incidence of diseases causing lymphadenopathy along with the demographics of the population under study, and to correlate site and size of lymphadenopathy with the histopathological diagnosis. Materials and Methods: A total of 163 patients whose lymph nodes biopsies were performed from January 2015 to June 2018 were included in the study. All demographic and laboratory data were recorded on a proforma and analyzed using SPSS version 22. Results: A total of 163 biopsies were studied with ages ranging from 03 to 96 years. Female patients were 57.05% and male patients 42.94%. In the studied cases, 74.84% were found to be non-neoplastic, 13.5% neoplastic while 11.65% of cases biopsies were either unremarkable or non-lymphoid tissue was biopsied. Reactive hyperplasia was the commonest lesion accounting for 50.3% of cases, followed by tuberculosis (23.3%), metastatic carcinoma (6.2%), lymphoproliferative disorders (1.84%), Hodgkin’s lymphoma (3%), non-Hodgkin’s lymphoma (2.45%) and non-caseating granulomatous lymphadenitis (1.22%) respectively. Lymph node size was found to be greater than 2cm in only 25.7% of cases. Conclusion: Reactive hyperplasia and tuberculosis are the most common diagnosis in lymph node biopsies. Lymph node biopsy is a diagnostic and reliable histologic investigation to differentiate non-neoplastic lesions from neoplastic lesions, and further classify the disease based on microscopic findings in both cases.